Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s10904-021-02142-7
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Zinc Oxide Nanoparticles (ZnO NPs) for Effective Degradation of Dye, Polyethylene and Antibacterial Performance in Waste Water Treatment

Abstract: At present, there is a vital need for river water purification by developing new approaches to eliminate bacterial biofilms, textile dyes, and Low-Density Polyethylene (LDPE) plastics that pose severe threats to human and environmental health. The current work put forward the construction of an eco-friendly green strategy to synthesize zinc oxide nanoparticles (ZnO NPs) using areca nut (Areca catechu) extract and their application to tackle the challenges in water purification. Prepared biogenic NPs were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…On the other hand, the comparable results for two ZnONPs in S. aureus [67]. In addition, Raghavendra et al [68] reported that among all the tested bacterial pathogens, E. coli at 50 µg/ml concentration showed the highest inhibition of biofilm activity upon treatment with the biosynthesized ZnONPs, followed by the highest growth curve, cellular leakage, and potassium ion efflux.…”
Section: Antimicrobial Activity Of Znonpsmentioning
confidence: 74%
See 1 more Smart Citation
“…On the other hand, the comparable results for two ZnONPs in S. aureus [67]. In addition, Raghavendra et al [68] reported that among all the tested bacterial pathogens, E. coli at 50 µg/ml concentration showed the highest inhibition of biofilm activity upon treatment with the biosynthesized ZnONPs, followed by the highest growth curve, cellular leakage, and potassium ion efflux.…”
Section: Antimicrobial Activity Of Znonpsmentioning
confidence: 74%
“…Likewise, Vinayagam et al [163] showed that ZnONPs could efficiently degrade more than 88% of methylene blue dye within 270 min. Also, Raghavendra et al [68] reported that the biosynthesized ZnONPs exhibited great photodegradation of Methylene Blue, Rhodamine-B and Nigrosine dyes under sunlight irradiation at different time intervals. Furthermore, the decolorization percentages of the methylene blue and Eosin Y dyes were 84% and 94%, respectively, which indicate an efficient degradation of the ZnONPs [114].…”
Section: Environmental Applications Of Znonpsmentioning
confidence: 99%
“…Similar to the current investigation, numerous phytogenically/greenly synthesized ZnO-NPs were characterized using the XRD analysis [ 66 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, weight loss of the polymer confirmed the photocatalytic activity of ZnO nanoparticles. 36 A special experiment conducted under the theme of water purification revealed that zinc oxide nanoparticles (ZnO) synthesized from areca nut (Areca catechu) had the capacity to degrade LDPE films. The degradation was bought by the photocatalytic property of the ZnO nanoparticles.…”
Section: Nanoparticles In Plastic Degradationmentioning
confidence: 99%